Evaluación de pérdidas térmicas en el sistema de generación y distribución de vapor en el hospital "Dr. Julio Enrique Paredes" Unidad Oncológica Solca Tungurahua, año 2014. Propuesta para optimización del aprovechamiento energético. - Cabrera Anda, Santiago Paúl (2016)
The problem is focused on the field of thermal efficiency for power generation and distribution of steam. Itis justified from current government policies related to the new energy matrix and its focus on efficiency. The hypothesis proposes: The reduction of heat losses in the distribution system and steam generation allow to obtain energy savings and increase energy efficiency, which will optimize the degree of energy efficiency at the Power Machines Area belonging to "Dr. Julio Enrique Paredes" SOLCA Tungurahua Oncology Unit Hospital. The theoretical framework exposes concepts related to Evaluation of thermal losses and energy balance. The methodology applied techniques such as observation and measurement using digital tools such as thermal camera and psychrometer for obtaining data. The proposal suggests using 6,9 kW of 88,6 kW waste heat in the exhaust gases from the chimney by heat exchange to obtain 108 kg/h of additional hot water for sanitary use, representing an increase of 1,2 % in the overall efficiency of the steam generation process.